INTEGRATING URBAN FARMING INTO THE SRI LANKAN RESIDENTIAL ARCHITECTURE AND BUILT ENVIRONMENT - Kulathunga, S.; Perera, U.; Udawattha, C. (Faculty of Management Studies and Commerce, University of Sri Jayewardenepura, 2022)
Sri Lanka is facing a devastating food crisis in the recent years due to the economic collapse in the country. Day by day, the access to food is decreasing while the prices are increasing. Urban agriculture is viewed as a workable solution for urban food issues in developed nations. However, Sri Lanka is still in the early stages of urban farming. There is still need for investigation about the potential applications of urban framing technology in Sri Lanka's built-up urban environment. The project will examine how to set up urban farming systems that might be used in high-rise structures, homes with yards, and low-income slums, as well as develop instructions for the general public on urban farming. Additionally, it will look at how urban farming practices might be related to residential building architecture. Following the preliminary research, a series of product prototypes will be made using soilless farming techniques. These will undergo testing and modifications to
Keywords: Building construction technology, urban agriculture technology, urban farming, architectural design